Comparison study of energy efficiency activities programs among the selected region and countries: lessons learned for Malaysia - Ab. Ghani, Mohd Ruddin; Abdulzahra, Ali Abdulhasan; Tamjis, Mohamad Rom; Mohamed Khairuddin, Mohamed Syafiq Akmal; Liaw, Geok Pheng; Saif T. H.; Alwahib, Ghassan Jawad Kadhim; Ahmed, Dawood Saleem; Zulkefle, Ahmad Aizan (Asian Research Publishing Network (ARPN), 2016)
This study reviews the contemporary tendencies in energy efficiency performance in chosen regions and countries. It also reviews the energy efficiency strategies and activities accomplished in these countries which pursue the program of reduction in energy consumption while maintaining the comfort level. These become the objectives and today’s energy efficiency requirement. This study also aims to highlight these activities and the outcomes of the energy efficiency implementation. The extent of this action and its effectiveness is being ascertained. The indicator used to evaluate the Energy Efficiency activities is the Energy Intensity Indicator which is provided by International Energy Agency (IEA). The reports and measurements of the International Energy Agency (IEA) are considered in order to make comparison among the selected countries. The main reason of focus on Energy Intensity levels is because this indicator reflects the result of all activities in different sectors and make sense which country has fulfilled the requirement of Energy Efficiency. The regions and countries are selected on the basis that their level of achievement in the energy efficiency programs are high. However, comparison is still made because each region and country has different emphasis and focus. Despite that Malaysia is a developing country, the achievement towards satisfactory energy efficiency implementation can be considered as encouraging and can only advance further if energy efficiency practice in these selected countries will be learned.